# substitution method

posted by
**seth**
.

-x-4y=-14 2x=y+1

Let's look at your two equations.

-x - 4y = -14

2x = y + 1

Let's solve the second equation for y:

y = 2x - 1

Now let's substitute (2x - 1) for y in the first equation:

-x - 4(2x - 1) = -14

-x - 8x + 4 = -14

-9x + 4 = -14

-9x = -18

x = 2

Substitute 2 for x in the second equation and solve for y:

2(2) = y + 1

4 = y + 1

y = 3

Check these values with the original equations. It always helps to check your work!

I hope this will help.